Noticias de la literatura chilena en Buenos Aires - Carlos Walker (Cuadernos LIRICO)
As part of a research dedicated to the Argentine literary field in 1969, we examine a series of events corresponding to the circulation of Chilean literature in Buenos Aires. In particular, this paper focuses on an anthology of Chilean narrative published by Jorge Alvarez press; on the publication of a book by Manuel Rojas; on the varied comments made on the most recent books by Pablo Neruda and Nicanor Parra; and on the important critical reception of Antonio Skármeta's Desnudo en el tejado. In this way, we propose a panorama of the presence of Chilean literature in Buenos Aires at the end of the 1960s. At the same time, the circulation and critical reception of these texts form a repertoire of heterogeneous manifestations which allows us to account for specific characteristics of the Argentine literary field of the period.